2014
DOI: 10.1111/nmo.12446
|View full text |Cite
|
Sign up to set email alerts
|

Variant parameter values—as defined by the Chicago Criteria—produced by ManoScan and a new system with Unisensor catheter

Abstract: Both systems can measure esophageal motility appropriately; nevertheless, we confirmed that the two systems showed different values of the parameters defined by the Chicago criteria. These differences should be recognized to evaluate esophageal motility precisely.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
64
2
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(72 citation statements)
references
References 9 publications
2
64
2
4
Order By: Relevance
“…The first HRM system that became commercially available was ManoScan®, and the Chicago Classification has been determined mainly based on its findings. It has been reported that parameters such as the DCI, intrabolus pressure, and IRP (but not contractile front velocity) have significantly higher values with Starlet® than with ManoScan® [16]. Accordingly, when using Starlet®, investigators should be aware of the potential for overestimating the results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The first HRM system that became commercially available was ManoScan®, and the Chicago Classification has been determined mainly based on its findings. It has been reported that parameters such as the DCI, intrabolus pressure, and IRP (but not contractile front velocity) have significantly higher values with Starlet® than with ManoScan® [16]. Accordingly, when using Starlet®, investigators should be aware of the potential for overestimating the results.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, when using Starlet®, investigators should be aware of the potential for overestimating the results. The upper limit of IRP was set to 25 mm Hg and the diagnostic criteria of jackhammer esophagus was set to at least 2 swallows with DCI >12,000 mm Hg·s·cm to account for differences in IRP and DCI according to the type of HRM catheter used [16]. Thus, our 2 patients with absent contractility and 1 patient each with IEM and fragmented peristalsis are considered to have truly weakened peristalsis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many indications that the Chicago Classification has been picked up globally, meaning that, after following the diagnostic algorithm, a gastroenterologist in Japan would come to the same final diagnosis as a gastroenterologist in the USA or Europe. Normal values for each system have been produced, as also described in this issue …”
Section: A New Diagnostic Technique: High‐resolution Manometrymentioning
confidence: 99%
“…Manometric data were analyzed using special software (Star Medical, Inc.) that had a function that was similar to the e-sleeve function. Kuribayashi et al [14] reported that the Starlet with a Unisensor catheter could evaluate esophageal motility precisely. TLESRs were evaluated according to previously published criteria for HRM reported by Roman et al [15], as follows: (1) absence of swallowing for 4 s before and for 2 s after the onset of LES relaxation; (2) the 4-s integrated relaxation pressure measured within the LES relaxation was 50% or less of the basal LES pressure; (3) the presence of swallowing was allowed if the LES relaxation duration was longer than 10 s in the absence of multiple swallows; and (4) inhibition of the crural diaphragm was also taken into account (fig.…”
Section: Methodsmentioning
confidence: 99%